Adult vocational decision, career satisfaction and future intention: Insights from the hospitality industry. Issue 12 (12th December 2016) - Zopiatis, Anastasios; Theocharous, Antonis L.; Constanti, Panayiotis
Abstract : Purpose: This study aims to examine the association between the elements which influence the career decision-making process of tenured hospitality employees and their existing level of career satisfaction (CSat) and future intention. Design/methodology/approach: Adopting a quantitative approach, a questionnaire survey collected data from 564 individuals working as full-time employees at all levels of the hierarchy in four- and five-star hotel establishments in Cyprus. Structural equation modeling analysis, preceded by exploratory factor analysis, was utilized to assess the constructs' relationships and address the postulated hypotheses. Findings: The results suggest that accurate job-person fit, reflective career awareness and the individuals' pragmatic occupational perceptions, positively influence their CSat and, subsequently, strengthen their intention to remain and progress within the industry. Research limitations/implications: The study's setting, the Cyprus hospitality industry, a Mediterranean seasonal destination with unique operational characteristics, may limit the generalizability of the findings to business environments in other regions. Practical implications: Insights are of interest and value to stakeholders, including academic scholars wishing to build on this investigation, industry professionals striving to revitalize interest toward relevant professions, career counselors' vocational decision guidance tactics and strategies and individuals envisioning a prosperous hospitality career. Originality/value: The paper enhances and enriches our conceptual knowledge of a relatively barren landscape, investigating the behavior of mature employees' choice of a hospitality career.